Arapça öğretiminde dil yeteneklerinin geliştirilmesinde şarkı kullanımı - Alshawabkeh, Esraa Khaled Yousef (My University, 2018)
Bu araştırmada; ikinci bir dil olarak Arapçayı öğrenenler nezdinde dinleme, konuşma, yazma ve okuma gibi Arapça dil becerilerinin gelişiminde şarkı kullanımının etkisinin bilinmesi hedeflenmiştir. Araştırma, Marmara Üniversitesi’nde hazırlık sınıfında Arapça öğrenen Türk kız öğrenciler üzerinde yapılmıştır. Araştırmacı, şarkıların bir araya getirilerek, analiz edilip sınıflandırıldığı çözümleyici-betimleyici yöntem ve deneysel yöntem olmak üzere iki yöntem izlemiştir. Araştırma grubu 2016-2017 eğitim-öğretim yılında Marmara Üniversitesi İlahiyat Fakültesi hazırlık sınıflarında öğrenim gören 9 kız öğrenciden oluşmaktadır. Bu grup üzerinde uygulanan ön test ve son testin alan sonuçları SPSS ile analiz edilmiştir. Bu çalışmanın sonucunda Arapça dil öğretiminde şarkı kullanımının öğrencilerin dilin dört becerisini geliştirdiği, öğrencilerin derste ilgisini çektiği ve dil öğrenme sürecini eğlenceli hale getirdiği tespit edilmiştir.

This study aims to examine the effectiveness of using songs to develop Arabic language skills of students, who learn Arabic as a second language. To answer the questions of this study, the researcher adopted descriptive analytical and experimental methods. The sample of the study consists of nine students from the preparatory year at the Faculty of Theology at the Marmara University in Istanbul. The researcher used the one group as an experimental group. The songs used with them in the second term of the academic year (2016-2017), these included a skills test of 6 main questions, which was designed to be used as a pre-post test. The results of the study were analyzed using the SPSS program. The study indicated that there are statistically significant differences in the main scores of skills test in favor of experimental group in the post application. Which means that the use of songs in the teaching of Arabic language skills has had an effective impact on the development of Arabic language skills among students.The researcher recommends the use of songs in the educational process of teaching the Arabic language as a second language, due to the positive impact on cognitive, emotional, aspects of learning, which in turn leads to improvements of the performance of student´s language skills in general.
Keywords: Anadili Arapça Olmayanlar using songs; Arabic language; Arap dili; Arap Dili Eğitimi; as a second language; Gramer; Grammar; Öğrenim ve öğretim; Study and teaching; Şarkıların Kullanımı; teaching Arabic; Turkey; Türkiye